Pengaruh Vocabulary Self-collection strategi terhadap penguasaan kosakata siswa kelas delapan SMPN 1 Matur - Milawati, Yohana; Kardena, Absharini; Melani, Melyann; Eliza (ELP (Journal of English Language Pedagogy), 2025)
This study was conducted to address several problems in students’ English learning, particularly in vocabulary acquisition. First, students faced difficulties in learning and retaining vocabulary. Second, they had not received adequate English instruction at the elementary school level. The purpose of this research was to examine the effectiveness of the Vocabulary Self-Collection Strategy (VSS) in improving students’ vocabulary mastery. A pre-experimental design with a one-group pretest-posttest approach was used. The population consisted of 8th-grade students at SMPN 1 Matur in the 2024/2025 academic year, with a total sample of 18 students selected through total sampling, as only one class was available. Data were collected using a vocabulary test comprising 20 items. The mean pretest score was 30.56, which increased significantly to 58.06 in the posttest. The hypothesis test showed that the alternative hypothesis (Ha) was accepted, with a significance value (Sig. 2-tailed) of 0.000, which is lower than ? = 0.05. This indicates that the use of VSS had a statistically significant effect on students’ vocabulary mastery. The posttest scores demonstrated clear improvement, confirming the effectiveness of the strategy. Therefore, it can be concluded that VSS is an effective method for enhancing vocabulary learning among 8th-grade students at SMPN 1 Matur.